Concealment of Parkinsons disease prevalence and impact on health and quality of life - Badera Naamneh-Abuelhija; Michal Kafri; Meir Kestenbaum; Shmuel Giveon; Sharon Kamah; Sarit Shved; Galit Yogev-Seligmann (Scientific Reports)
Abstract Concealment of diagnosis in chronic conditions has proven benefits as a coping strategy to avoid stigmatization and discrimination and allows people to be treated “normally” by society. However, concealment is related to negative health, physical, quality of life outcomes, exhaustion and loneliness. In addition, diagnosis concealment has a detrimental impact on self-management behaviors. In Parkinson’s disease (PD), information regarding the aspects related to concealment is limited. A better understanding of the contributors and consequences of concealment in PD may facilitate the development of strategies to support patients who conceal. We conducted a cross-sectional study to explore concealment in PD by examining rates of diagnosis concealment and associations of concealment with socio-demographic factors, self-management behaviors, stigma, social support, and quality of life. The study was conducted at an outpatient movement disorders clinic or at the participant’s home, at the participant’s preference. One hundred and fifty people with PD completed questionnaires assessing disclosure of their diagnosis,  socio-demographic variables, disease severity, self-management behaviors (knowledge, activation, exercise), stigma, social support, and health-related quality of life (HRQoL). Differences between disclosers and concealers were analyzed and associations between disclosure, stigma, social support and emotional aspects of HRQoL were tested using mediation models. Close to one-quarter (22.7%) conceal their PD diagnosis from their family. Concealers were more often women, Muslim, religious, and lacking academic degrees compared to disclosers. Concealers also had lower patient activation, and less social support. They engaged less in physical activity and experienced greater stigma. Concealment had a significant total effect on lower emotional aspects of HRQoL, mediated by greater stigma but not by social support. Healthcare providers should be attuned to both the prevalence of PD diagnosis concealment and its detrimental impacts on patients’ emotional support needs and facilitation of health behaviors. Moreover, treating neurologists should deliver diagnoses carefully, discuss disclosure consequences, maintain open dialogue on concealment, and advise informing family. Interventions targeting stigma reduction in this population may have downstream benefits for emotional aspects of HRQoL. Trial registration: NCT05209698; Registration Date: 23/1/2022.